Analisis Kepemimpinan Teman Sejawat dalam UKM Persekutuan Mahasiswa Kristen Institut Pertanian Bogor - Fabio Ezra Cannavaro Sitanggang; Impana Cibro (Policy, Law and Political Research Center, 2022)
The leader is someone who is elected either by acclamation or democracy, who is then trusted as the captain to lead a ship. Leaders will influence someone in their actions in an association or organization. A good leader will be better able to protect his members. An organization will run as expected by its members if the leader is not only an errand boy like a boss, but is able to participate in encouraging his members to do something. Leadership is the basis of the main abilities and skills to organize and influence other people in an organization, to carry out tasks and authority well. It is the same with UKM PMK which has a leader with a leadership type in carrying out his duties as a leader. There are eight styles of leadership that can be carried out according to the situation and conditions of the organization being run.